Pengaruh Brand Image, Harga, dan Kualitas Produk Terhadap Minat Beli Generasi Z Pada Produk Thrift Fashion di HM Bulakelor Brebes - Amelia; Akbar Nuur Purnama D.W; Ari Kristiana; Dumadi; Kukuh Arianto Wibowo (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
The global fashion industry is currently experiencing significant changes in consumer behavior, where the previously dominant fast fashion trend is starting to be replaced by the phenomenon of sustainable fashion, including thrift fashion products. The thrifting phenomenon is no longer just buying used goods, but rather part of the lifestyle and expression of Generation Z identity. This study aims to determine the influence of brand image, price, and product quality simultaneously on Generation Z's purchasing interest in thrift fashion products at HM Bulakelor. The research population is all consumers of thrift fashion products at HM Bulakelor Brebes, especially Generation Z, who have an average of 10-20 consumers per day or as many as 501 Gen Z per month. The research sample is 84 consumers with a sampling technique using the Slovin formula with a margin of error of 5%. Data collection uses a questionnaire with instrument testing using validity and reliability tests. Data analysis uses multiple linear regression analysis with the help of SPSS. The results of the study show that partially brand image and product quality have a significant effect on purchasing interest, while price does not have a significant effect on purchasing interest. Simultaneously, brand image, price, and product quality significantly influence Generation Z's purchase intention for thrift fashion products at HM BulakelorBrebes